Down and dirty pictures Miramax, Sundance, and the rise of independent film - Biskind, Peter 1940- (Simon & Schuster, 2004)
Down and Dirty Pictures chronicles the rise of independent filmmakers and of the twin engines--Sundance and Miramax-that have powered them As he did in his acclaimed Easy Riders,Raging Bulls Peter Biskind profiles the people who took the independent movement from obscurity to the Oscars, most notably Sundance founder Robert Redford.
Includes bibliographical references and index
Keywords: Miramax Films - Histoire; Sundance Film Festival - Histoire; Miramax Films -- History; Sundance Film Festival -- History; Geschichte 1990-2004; Cinéastes indépendants - États-Unis; Experimentele filmkunst; Filmfestivals; Filmindustrie; Geschichte; Independent filmmakers -- United States; Unabhängiger Film; USA